Analysis of some aspects of microorganisms application for inorganic and minerals treatment - Lazariev, V. G.; Drazhnikova, A. V.; Karpenko, V. I. (Problems of Environmental Biotechnology, 2014)
The article discusses the possibility of integrating multiple methods of biotechnology, namely the elimination of oil pollution using biodegradation, biosorption of heavy metals, obtaining of microbial nanoparticles, technology of microbial fuel cells and others. Authors defined conditions and features of their possible integrated application.